Knowledge, attitudes and practices related to African Swine Fever within smallholder pig production in northern Uganda - Chenais, E.; Boqvist, Sofia; Sternberg Lewerin, Susanna; Emanuelson, Ulf; Ouma, Emily A.; Dione, Michel M.; Aliro, T.; Crafoord, F.; Masembe, C.; Stahl, K. (Hindawi Limited, 2017)
Uganda is a low-income country with the largest pig population in East Africa. Pig keeping has a large potential, commercially and as a tool for poverty reduction, but African swine fever (ASF) is a major hurdle for development of the sector. The objective of this study was to evaluate knowledge, attitudes and practices related to ASF in the smallholder pig production value chain in northern Uganda. The study included three separate series of participatory rural appraisals (PRA), comprising purposively selected farmers and other actors in the pig production value chain. In the PRAs, various participatory epidemiology tools were used. A total of 49 PRAs and 574 participants, representing 64 different villages, were included. The results indicate that participants were well aware of the clinical signs of ASF, routes for disease spread and measures for disease control. However, awareness of the control measures did not guarantee their implementation. A majority of middlemen and butchers acknowledged having sold live pigs, carcasses or pork they believed infected with ASF. Outbreaks of ASF had a strong negative impact on participants’ socio-economic status with loss of revenue and reversal into more severe poverty. In conclusion, lack of knowledge is not what is driving the continuous circulation of ASF virus in this setting. To control ASF and reduce its impact, initiatives that stimulate changes in management are needed. Because the behaviour of all actors in the value chain is largely influenced by the deep rural poverty in the region, this needs to be combined with efforts to reduce rural poverty.